Level of knowledge and acceptance of hormone replacement therapy in women over 39 years - Solsol, Gloria (2015)
OBJECTIVE: To establish the level of knowledge and acceptation of hormonal replacement therapy in patients over 39 Yearold. DESIGN: Transversal descriptive study. SUBJECTS: 212 patients over 39 yearold. LOCATION: Outpatient Gynecology Service of Cayetano Heredia National Hospital between February and April 1995. RESULTS: 84% were climacteric or menopausal. Most known symptoms were neuropsychiatric, 72% knew about treatment, only 6% used it, 97% accepted HRT and 61% were willing to receive HRT for live, but only 25% knew the benefits. There was fear of bleeding and gestation in 37% and 58% respectively. CONCLUSION: Patients with better education bad more knowledge of HRT benefits. Patients who receive HRT know more about the benefits of hormonal therapy.